Bone metastasis from malignant phyllodes breast tumor: report of two cases. Issue 1 (December 2016) - El Ochi, Mohamed; Toreis, Mehdi; Benchekroun, Mohamed; Benkerroum, Zineb; Allaoui, Mohamed; Ichou, Mohamed; El Khannoussi, Basma; Albouzidi, Abderrahman; Oukabli, Mohamed
Abstract Background Phyllodes tumors are rare fibroepithelial tumors accounting for less than 1 % of all breast neoplasms. They are malignant in 20 % of cases. Only a few cases of malignant phyllodes tumors metastatic to bone have been reported. Case presentation Case 1: A 40 year-old white woman presented with three-week history of pain and functional impairment of the left lower limb. Her clinical past was remarkable for previous left mastectomy and radiotherapy for malignant phyllodes tumor performed one year ago. Computed tomography revealed a moth-eaten appearance of the left femoral head. The patient underwent computed guided femoral head biopsy. Pathological findings were consistent with metastatic malignant phyllodes tumor. The patient received ifosfamide and adriamycin chemotherapy. She is doing well without any evidence of progression on her imaging follow- up after 8 months. Case 2: A 48 year-old white woman, with history of bilateral mastectomy and radiotherapy for malignant phyllodes tumor performed one and two year ago, presented with four-week left lower quadrant abdominal pain. Computed tomography and magnetic resonance imaging revealed a solid aggressive osteolytic mass of the left iliac bone with extensive soft tissue invasion. Biopsy of the tumor was performed and showed a sarcomatous proliferation consistent with metastatic malignant phyllodes tumor. The patient received the same chemotherapy regimen as in the first case but without any response on her imaging follow up after 6 months. Conclusion Malignant phyllodes tumor is a rare and aggressive fibroepithelial neoplasm. An accurate diagnosis of metastases should be based on clinicopathological correlation allowing exclusion of differential diagnoses. The goal of successful managing this tumor is early detection and complete resection prior to dissemination.